Screening tools for targeted comprehensive geriatric assessment in HIV-infected patients 50 years and older. (September 2019) - Sangarlangkarn, Aroonsiri; Apornpong, Tanakorn; Justice, Amy C; Avihingsanon, Anchalee
Many people living with HIV (PLWH) are aging with geriatric syndromes, but few undergo comprehensive geriatric assessment (CGA) due to limited resources. Our study evaluates tools to identify aging PLWH who may forego CGA. We conducted a cross-sectional study on 357 PLWH ≥50 years old at the Red Cross, Thailand. Tools evaluated were the Veterans Aging Cohort Study Index (VACSI) and G-8, which is predictive among older cancer patients. CGA consists of eight tests: history of fall within 12 months, timed-up-and-go test (TUG), activities of daily living (ADL), instrumental ADL (IADL), Montreal cognitive assessment (MoCA), Thai depression scale (TDS), mini nutritional assessment (MNA), and HIV symptom index (HSI). We considered ≥2 impaired domains on CGA to be abnormal results. Forty-nine percent (n = 175) had ≥2 impaired domains on CGA. Few participants had experienced a fall (11%) or abnormal TUG/ADL/IADL (<2%), and only MoCA/TDS/MNA/HSI were analyzed. A VACSI < 17 produces 85% sensitivity (Se) and 30% specificity (Sp) (area under the ROC curve [AUC] = 63, 95%CI 58–69) and G-8 > 15.5 produces 90%Se and 33%Sp (AUC = 74, 95%CI 69–79) in identifying patients with <2 impaired domains. A G-8 > 13.5 produces 91%Se and 77%Sp (AUC = 89, 95%CI 86–92) in ruling out abnormal nutrition. Patients with VACSI < 17 and G-8 > 15.5 may forego CGA due to low likelihood of abnormal cognition, mood, nutrition, or symptom burden.